The socialist realism and its (in)definitions - Andrade, Homero Freitas de (Literatura e Sociedade, 2010)
Starting from a brief view of the russian and soviet literary vanguards of the two first decades of the 20th century, this essay is going to discuss questions concerning the formation, instauration, developments and production of the so-called socialist realism, which was in force in the USSR from 1932 onwards. Also, the roots of that alleged method of artistic representation in the russian literary and critical tradition of the 20th century are here studied.